Penerapan Job Sheet Praktek Instalasi Motor Listrik di Sekolah Menengah Kejuruan - Ikra, Ikra; Hambali, Hambali (Jurnal Pendidikan Teknik Elektro, 2025)
— The learning process is a series of activities that occur throughout a person's life. To help students carry out good learning activities, a learning system is needed. The learning system requires various learning media called teaching materials. Types of teaching materials involve the use of information sheets, operation sheets, job sheets, workshop handouts, and modules, aiming to ensure the smooth implementation of practical activities. For students to carry out practical activities, it is important to provide guidance on using learning media or teaching materials, such as job sheets. The purpose of this study was to improve student learning outcomes after implementing the Electric Motor Installation practical worksheet for class XI TITL at SMK Negeri 2 Panyabungan and to determine the validity, practicality, and effectiveness of the job sheet used as a learning medium for the Electric Motor Installation element. This type of research is quantitative research. Quantitative methods are numerical or quantity-based and often involve statistical analysis. The population of this study was all students of the Electrical Power Installation Engineering Study Program (TITL) at SMKN 2 Panyabungan as many as 36 people with a sample of 12 people. The research instruments were tests and questionnaires. Data were analyzed using normality tests, homogeneity tests, and hypothesis tests. Based on the research results, it can be concluded that the application of the electric motor installation practical worksheet has a positive effect on student learning outcomes.